Hypertension onset in a 12-year-old adolescence with negative family history: a rare presentation of essential hypertension with good response to diltiazem/prazosin combination - Shalihin, Mohd Shaiful Ehsan; Harun, Zulkifli; Osman, Iskandar Firzada (2018)
Essential hypertension in adolescence is increasing in trend worldwide in view of increasing prevalence of childhood obesity and sedentary lifestyle. Generally, the younger the onset of the hypertension, the more likelihood of secondary causes is suspected. It is a dilemma among primary care providers to decide which case should be assessed further for secondary hypertension. We report a case of 14 year-old adolescent male diagnosed with hypertension for past 2 years, with suboptimal blood pressure control at primary care. He is not morbidly obese. He is non smoker with good academic performer. He had good family support. All his family members are normotensive with ideal body weight. He has no clinical and biochemical features of secondary hypertension from initial assessment. In view of worsening blood pressure control on different first line drugs, we referred this patient for further work up and shared care with endocrinology team. However, the results turn up to be normal. Surprisingly, his blood pressure is responsive well with prazosin and diltiazem during adjustment period prior to assessment for renovascular hypertension. His hypertension is well controlled till now. This case had proved that essential hypertension is still possible in early non morbid obese adolescent despite negative family history of hypertension. Even though alpha blocker and non dihydropyridine calcium channel blocker are not first line antihypertensive agents, treatment should be individualized and they still play role in those with resistant hypertension in adolescent, provided appropriate assessment had been done either in primary or tertiary care for secondary causes.